Intraoperative 3D quantitative magnetic resonance imaging in paediatric brain tumour surgery - Per Nyman; Rafael Turczynski Holmgren; Emma Nordh; Anna Ljusberg; Oscar Snödahl; Frederik Testud; Ida Blystad; Peter Lundberg; Anders Tisell (PLoS ONE, 2026)
Purpose • To investigate if R 1 and R 2 can reliably be measured using 3D quantitative MRI in an intraoperative setting when paediatric brain tumour surgery is performed. • To determine whether B 1 + inhomogeneities affect R 1 and R 2 measurements in normal-appearing white matter and the thalamus, respectively, and how R 1 and R 2 measurements are affected by different coils. • To assess how the relaxation parameters of brain tissue are affected by the intraoperative setting. Methods The accuracy of R 1 and R 2 , the effect of B 1 + -field inhomogeneity and how the flex coil position affected R 1 and R 2 were evaluated, both pre- and intraoperatively during surgery. Ten patients were recruited, six girls and four boys aged 2–15 years, with varying tumour entities, all referred to surgery with intraoperative MR. The patients were scanned using a head coil preoperatively and flex coils intraoperatively. Control experiments were performed on phantoms in various positions, equivalent to the patient positions. ROIs (Regions of Interest) were positioned in areas representing normal-appearing matter. Relaxation rates R 1 and R 2 were calculated from 3D-quantification using an interleaved Look-Locker acquisition sequence with T 2 preparation pulse (3D-QALAS) data. Results There was a significant increase of R 2 in the intraoperative setting compared to the preoperative 3D-QALAS measurements. In contrast to the patient examinations, control experiments using relaxation phantoms did not demonstrate similar differences. Conclusion Relaxometry is feasible in the intraoperative setting. The detected differences between the quantitative R 2 values in tissue pre- and intraoperatively seem to be explained by the physiological conditions characterising the surgical situation.